CITIZENSHIP IN THE FACE OF SOCIOECONOMIC VULNERABILITY AND THE PROVISION OF CIVIL JUSTICE: A VISION AIMED AT BETTER EFFICIENCY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The aim is to analyze the citizenship aspects of people in socio-economic vulnerability who need civil justice; to present the legal institutions that help the socio-economically vulnerable; to indicate which legal institutes are applicable for this purpose. And, the research problem: In view of the civil legal institutes in place to help the socio-economically vulnerable, is it possible to improve their effectiveness? How?The research was carried out using the deductive method, with a bibliographical review and analysis of legislation and documents, as well as exploratory research to understand and describe the object. And, through explanatory research to solve the problem, the results of which point to suggestions aimed at improving the effectiveness of the institutes analyzed in the final considerations of this article.